PRONUNCIATION PROBLEMS AND THE APPLICATION OF PROCESS SKILL APPROACH: A CASE STUDY OF MECHANICAL ENGINEERING STUDENTS AT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Yasinta Farahsani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Mastery of English as an international language is a demand that must be developed along with the times. In one of the subjects that must be taken by students of Mechanical Engineering UMY is English: Writing and Presentation. Some of the difficulties encountered in making presentations were their lack of knowledge about public speaking, so that the presentations seemed monotonous and unattractive. In addition, when making presentations in English, the biggest obstacle is the pronunciation problem. In this study, the writer examined the application of appropriate learning method for pronunciation learning so that students were able to optimally pronounce each word in English. In the results of observation and simulation, the writer found 4 (four) students' difficulties of learning English, 1) they tended to say in accordance with the spelling, 2) they found difficulty with vocabulary ending in '-ed', 3) they found difficulty with diphthong sounds, 4) they found difficulty in pronouncing words with sounds that are almost the same in other words. Thus, drilling is done to improve it which includes manner of presentation and pronunciation.